Point-to-Multipoint Optical Networks Using Coherent Digital Subcarriers - Welch, Dave; Napoli, Antonio; Back, Johan; Sande, Warren; Pedro, Joao; Masoud, Fady; Fludger, Chris; Duthel, Thomas; Sun, Han; Hand, Steven J.; Chiang, Ting-Kuang; Chase, Aaron; et al. (Journal of lightwave technology, 2021)
A paradigm shift in optical communication networks is proposed, with the introduction of a new ecosystem of devices and components with the capability of transforming current point-to-point optical networks (with their entailed, limiting, electrical aggregation) into flexible, scalable and cost-effective point-to-multipoint networks. In the new architecture, which better aligns with the hub-and-spoke traffic patterns observed in today's metro and access network segments, interoperability across a variety of transceivers operating at different speeds is achieved using individually routed, digitally generated subcarriers. The first comprehensive demonstration of the technical feasibility of the proposed point-to-multipoint architecture based on digital subcarrier multiplexing is presented, along with the remarkable cost savings and simplification of the network it enables.